Perancangan Perbaikan Positioning Produk T-shirt Nakhoda Nusantara Berdasarkan Perceptual Mapping Menggunakan Metode Multidimensional Scaling dan SWOT Analysis - Yuniar, Wiwit Agi; Rohayati, Yati; Kusmayanti, Ima Normalia (Jurnal Ilmu Manajemen, 2022)
The purpose of this study is to design an improvement in positioning strategy by exploring consumer perceptions in choosing and buying t-shirt products. The object used in this study is the Nakhoda Nusantara brand. This study uses the method of multidimensional scaling (MDS) and SWOT analysis. The attributes used are material quality, color, price, design quality, comfort, attractiveness, fashionable, and brand reputation. Competitor brands determined in this study are 3Second, Owners, Screamous, Wadezig, and Byrazi. The number of samples used in this study were 90 respondents. Sampling using a nonprobability sampling method with a purposive sampling technique. The results of the analysis in this study are: (1) a positioning strategy on the priority attributes that are the weaknesses of the Nakhoda Nusantara t-shirt based on the Euclidean distance, namely attribute attractiveness and fashionable. These two attributes are the main considerations to make the Nakhoda Nusantara t-shirt superior to other competitors. (2) The results of perception mapping produce a stress value of 0.09300 and an R-Square value of 0.99196, so it can be said that this study is valid and reliable.